A Precision Capillary Coating System and Applications. Issue 3 (2nd July 2016) - Pan, Po-Ting; Hsieh, Ming-Che; Liu, Chao-Yuan; Pan, Chien-Wen; Zhao, Kai-Wen; Hsieh, Yu-Wen; Wang, An-Bang
Abstract: A precision direct patterning system based on capillary coating was developed to meet the requirements of a range of different applications. Silver ink with a viscosity of about 220 cP was initially used as a working fluid to study the effect of control parameters including the coater tip diameter, the coating velocity, the coating gap, and the back pressure. Quantitative analyses of the liquid bridge shape and wet film morphology, such as line thickness and width, were conducted to study the coating mechanism. A compact direct precision patterning desktop system with exchangeable coater modules was also developed for use in the laboratory, or even the home, to replace the tedious processes and cumbersome machines normally used. The application of a Hole Injection Layer on an OLED display panel was achieved and even the preparation of layers for costly biomedical processes involving antibodies were successfully demonstrated which shows the feasibility of this coating technique for different applications. The proposed coating system shows a very high material utility rate and has the potential to produce very complex patterns for research and industrial applications using material with a wide range of viscosity. Graphical abstract: